Synthesizing and staining manganese oxide nanoparticles for cytotoxicity and cellular uptake investigation - Omid, Hamed; Oghabian, Mohammad Ali; Ahmadi, Reza; Shahbazi, Narges; Hosseini, Hamid Reza Madaah; Shanehsazzadeh, Saeed; Zangeneh, Rashin Namivandi (Biochimica et biophysica acta, 2014)
For decades, contrast agents have been used to reduce longitudinal (T1) or transverse (T2) relaxation times. High toxicity of gadolinium-based contrast agents leads researchers to new T1 contrast agents. Manganese oxide (MnO) nanoparticle (NP) with the lower peril and good enough signal change ability has been offered as a new possibility for magnetic resonance imaging (MRI). The synthesized NPs were investigated for physicochemical and biological properties by X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscope, dynamic light scattering (DLS), inductively coupled plasma, enzyme-linked immunosorbent assay, and 3T magnetic resonance imaging. Due to physical contact importance of T1 contrast agents with tissues' protons, extremely thin layer of the surfactant, less than 2nm, was coated on NPs for aqueous stabilizing. The hydrophilic gentisic acid with low Dalton, around 154, did that role truly. Moreover, decreasing NP size to 5nm which increases available surface for the proton relaxation is another important parameter to reach an appropriate longitudinal relaxation rate. The NPs didn't reveal any side effects on the cells, and cellular uptake was considerable. The synthesized NPs represented a promising result in comparison to clinical gadolinium chelates, due to higher r1 relaxivity and lower toxicity. In addition to considerable signal change and cellular uptake, Prussian blue was tried on MnO NPs for the initial time, which can be observed within cells by pale blue color. •We synthesized the stable nanocolloid of MnO nanoparticles.•The prepared nanoparticles have a wide improvement in r1 relaxivity compared to other available clinical T1 contrast agents.•Cellular uptake of nanoparticles was considerable with simple incubation with protamine sulfate as a transfection.•MnO nanoparticles were successfully stained by Prussian blue for the first time.